63 Characterization of the right ventricular substrate participating in post-infarction ventricular tachycardia. (16th October 2019) - Walsh, K; Shah, R; Khan, S; Supple, G; Garcia, F; Frankel, D; Lin, D; Kumareswaran, R; Hyman, M; Arkles, J; Deo, R; Zado, E; et al.
Abstract : Background: The right ventricle (RV) is uncommonly implicated in post-infarction ventricular tachycardia (PIVT). The prevalence and features of RV substrate participating in PIVT are undefined. Objectives: To characterize critical RV substrate (CRVS) involvement in PIVT. Methods: We retrospectively reviewed 1065 patients with PIVT undergoing catheter ablation at our center from 2000 to 2017. Cases with CRVS defined by conclusive demonstration of participation to PIVT with activation, entrainment and/or pace mapping during sinus rhythm were included. Results: RV mapping due to suspected participation in PIVT was performed in 58/1065 patients (5.4%), age 65±11 years, 91% males, LVEF 30±13%, all with LBBB morphology VT. CRVS was identified in 26 patients (2.4%, 11 anterior infarcts, 13 inferior infarcts) (table 1 ) with: 1) critical components of the PIVT circuit defined with activation/entrainment mapping or VT termination with RV ablation (n=21), 2) presence of low-voltage abnormal electrograms with excellent pace-map for the targeted VT and non-inducibility following ablation (n=5). CRVS was most commonly located in the septum (77%) followed by the free wall (23%) (figure 1 ). An additional 14 patients had no demonstrated CRVS but underwent empirical RV septal ablation in the process of biventricular septal substrate modification. Non-inducibility of the targeted VT following CRVS ablation was achieved in 28/34 patients (82%, 4 patients not tested), with non-inducibility of any VT in 18/34 (53%). Conclusion: The RV contains critical substrate elements of PIVT in at least 2.4% of cases, most commonly involving the RV septum.